Comparable cellular and humoral immunity upon homologous and heterologous COVID-19 vaccination regimens in kidney transplant recipients - Körber, Nina; Holzmann-Littig, Christopher; Wilkens, Gesa; Liao, Bo-Hung; Werz, Maia L.; Platen, Louise; Cheng, Cho-Chin; Tellenbach, Myriam; Kappler, Verena; Lehner, Viktor; Mijočević, Hrvoje; Christa, Catharina; et al. (Frontiers in Immunology, 2023)
Background: Kidney transplant recipients (KTR) are at high risk for severe course of COVID-19 making effective vaccination a critical need. However, achievement of protective immunogenicity is hampered by immunosuppressive therapies. We assessed cellular and humoral immunity and breakthrough infection rates in KTR vaccinated with homologous and heterologous COVID-19 vaccination regimens. Method: We performed a comparative in-depth analysis of SARS-CoV-2-specific T-cell responses using multiplex Fluorospot assays and SARS-CoV-2-specific neutralizing antibodies (NAb) between three times hoVac (n = 18) and heVac (n = 8) KTR. Results: We detected SARS-CoV-2-reactive T cells in 100% of KTR upon third vaccination, with comparable frequencies, T-cell expression profiles, and relative IFN-γ and IL-2 production per single cell between homologously and heterologously vaccinated KTR. SARS-CoV-2-specific NAb positivity rates were significant higher in heterologously (87.5%) compared to homologously vaccinated (50.0%) KTR (P < 0.0001), whereas magnitudes of NAb titers were comparable between both sub-cohorts after third vaccination. SARS-CoV-2 breakthrough infections occurred in equal numbers in homologously (38.9%) and heterologously (37.5%) KTR with mild to moderate courses of COVID-19. Conclusion: Our data support a more comprehensive assessment of not only humoral but also cellular SARS-CoV-2-specific immunity in KTR to provide an in-depth understanding about the COVID-19 vaccine-induced immune response in a transplant setting